2021
DOI: 10.1016/j.nano.2021.102404
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of squalene-doxorubicin distribution and interactions within single cancer cell using Raman microspectroscopy

Abstract: Investigation of squalene-doxorubicin distribution and interactions within single cancer cell using Raman microspectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Based on the EPR effect, many nanomedicines have been developed, including polymer conjugates, polymeric micelles, liposome, nanoparticles, antibody drug conjugate, and so on, some of which are approved for clinical use, and more are in preclinical trials [ 25 ]. For example, recently squalene that is a triterpene in the cholesterol biosynthesis pathway widely distributed in nature, has been successfully developed as a nanoplatform for various therapeutic molecules and nucleoside analogues with gemcitabine, as well as doxorubicin and paclitaxel, and the the squalenoylated doxorubicin nanoassemblies exhibited much improved anticancer therapeutic efficacy with decreased cytotoxicity [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the EPR effect, many nanomedicines have been developed, including polymer conjugates, polymeric micelles, liposome, nanoparticles, antibody drug conjugate, and so on, some of which are approved for clinical use, and more are in preclinical trials [ 25 ]. For example, recently squalene that is a triterpene in the cholesterol biosynthesis pathway widely distributed in nature, has been successfully developed as a nanoplatform for various therapeutic molecules and nucleoside analogues with gemcitabine, as well as doxorubicin and paclitaxel, and the the squalenoylated doxorubicin nanoassemblies exhibited much improved anticancer therapeutic efficacy with decreased cytotoxicity [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…148 Rammal et al observed the distribution of doxorubicin (DOX) and its squalenoylated nanoparticles in cancer cells using Raman marker bands, 1211 and 1241 cm −1 , in the fingerprint region. 155 In addition, Fu et al described SRS imaging and quantification of TKIs imatinib and nilotinib using Raman peaks ∼1300 cm −1 ; in addition, the process of drug uptake into lysosomes was monitored simultaneously using TPEF. 156 Dong et al also employed polarization-sensitive SRS from CC stretching vibration in the fingerprint region of amphotericin B (AmB), an antifungal agent, to monitor its distribution in fungal cells.…”
Section: ■ Raman Spectroscopy For Diagnosticsmentioning
confidence: 99%
“…The potential of confocal Raman microspectroscopy as a label-free and non-destructive tool for molecular characterization of anticancer nanodrugs and their potential toxic effects on cells, was studied by Rammal and co-workers [ 51 ]. They investigated the activity of the anticancer chemotherapeutic drug doxorubicin within single murine lung carcinoma cells and human breast cancer cells.…”
Section: Spontaneous Raman Scatteringmentioning
confidence: 99%